2‐Alkyl‐3‐methoxypyrazines are potent attractants of florivorous scarabs (Melolonthidae, Cyclocephalini) associated with economically exploitable Neotropical palms (Arecaceae). Issue 9 (25th March 2018) - Maia, Artur Campos Dália; Santos, Geanne Karla Novais; Gonçalves, Eduardo Gomes; Navarro, Daniela Maria do Amaral Ferraz; Nuñez‐Avellaneda, Luis Alberto
Abstract: BACKGROUND: 2‐Alkyl‐3‐methoxypyrazines (MPs) are naturally occurring aromatic compounds involved in insect chemical communication as both pheromones and allelochemicals. Although rarely characterized in floral scents, they have been identified as major constituents in headspace samples from palm inflorescences and evidence pointed towards their function as attractive cues for scent‐oriented pollinators, as well as florivores. In this study, we investigated the occurrence of MPs in economically exploitable palms belonging to Acrocomia and Attalea through headspace floral scent analysis and assessed their role in the selective attraction of flower‐feeding cyclocephaline scarabs (Melolonthidae, Cyclocephalini) in field bioassays conducted in Brazil and Colombia. RESULTS: Three different MPs were identified among floral headspace samples of Acrocomia aculeata, Acr. intumescens, Attalea butyracea and Att. insignis : 2‐isopropyl‐3‐methoxypyrazine (IPMP), 2‐isobutyl‐3‐methoxypyrazine (IBMP) and 2‐( sec ‐butyl)‐3‐methoxypyrazine (SBMP). Their combined estimated total scent emissions per inflorescence ranged from 246 μg h −1 to 6.2 mg h −1 . Scented traps, individually baited with either IPMP or SBMP, resulted in species‐selective and high yield captures of Cyclocephala amazona and C. distincta, known florivores associated with over 20 different species of Neotropical palms. CONCLUSIONS: The identification of MPs as potent kairomones could prove instrumental in integrated pest management plans for these insects in emerging oil‐yielding crops in South America, including those of the wine palm ( Att. butyracea ) and macaw palms ( Acrocomia spp.). © 2018 Society of Chemical Industry Abstract : 2‐Alkyl‐3‐methoxypyrazines were identified as selective kairomones that could prove instrumental to integrated pest management plans for cyclocephaline scarabs associated with emerging oil‐yielding crops in Tropical America.